RANCANGAN BANGUN SISTEM KEAMANAN SEPEDA MOTOR MENGGUNAKAN RFID DAN ARDUINO - Mochamad Yusuf Romdoni; Fuad Fuad (Jurnal Ilmiah Sains dan Teknologi, 2019)
This study aims to discuss about designing and building a motorcycle security system with RFID and Arduino, this system was designed as a new breakthrough in building a motorcycle security by applying the development of information technology using RFID devices and Arduino which have been widely implemented in various business sectors that not careless from communication networks, while the main benefit is being able to help control the motorcycle security system more quickly and can be controlled through the network. The development method used in this study uses waterfall and the techniques used to describe the system using the program flowchart, with the construction of a security system with Rfid and Arduino technology is expected to be able to prevent motorcycle theft and easier to control effectively and efficiently.